Food Waste Management Strategy in Leni's Terrace Kitchen - Arzakhia Arzakhia; Zahra Aulia Putri (An International Journal Tourism and Community Review, 2025)
Waste is one of the main problems in development, especially in the provision of city facilities and infrastructure. Unorganized and improper waste disposal has caused various serious environmental problems such as loss of natural habitat, air pollution, decreased environmental aesthetic value, and pollution of water bodies. These impacts are felt directly by the community and also affect national development. Kitchen or kitchen is a room filled with equipment Cook from scale small until big For process food that will presented . This term common used in hotel and restaurant industry . Leni's Terrace, a restaurant standing family​ since 2023, born from love three grandchild to figure Grandma they , Oma Leni, who is known Because warmth and deliciousness her cooking . In the past , Grandma Leni often to entertain family and guests with various cuisine typical on the terrace of his house . Leni's Terrace now serve dish with Western, Asian and Indonesian nuances recipe Oma Leni's legacy , accompanied by atmosphere full of nostalgia that gives experience memorable culinary.​